Sediment of Soft Influence: The Study of Soft Power, Soft War, and Smart Power in the Serene Turmoil of Yoko Ogawa’s The Memory Police - Ibrahim, Zahraa Khairallah Johar (Tasnim International Journal for Human, Social and Legal Sciences, 2026)
The shifting landscape of international relations has spurred a transformation in the approach towards soft power, soft war, and smart power strategies. This evolution is driven by the recognition of the limitations of traditional hard power methods in achieving sustainable influence and control in an interconnected world. As countries adapt to global dynamics, the fusion of hard power and soft power tactics emerges as a strategic imperative to navigate complex geopolitical challenges effectively. In this regard, writers in different fields reflect it in their writings, especially in literature. On the top of the list is Yoko Ogawa who, paid much attention to the power dynamics. Thus, the study investigates these powers in Yoko Ogawa’s novel The Memory Police. The research examines the government’s systematic erasure of memories as a manifestation of subtle control. It highlights the contradictions inherent in the regime’s exercises of soft power, which ultimately lead to its failure to achieve its desired goals. It explores the psychological struggles faced by individuals subjected to oppression, and how they can draw on their cultural heritage as a source of soft power to confront authoritarian regimes.